Identification of Curvularia eragrostidis (Henn.) J.A.Mey. the Leaf Spot Pathogen of Oil Palm (Elaeis guineensis Jacq.) and It’s Control by False Elder (Peronema canescens Jack) Leaf Extract - Febriani, Anya Via; Kasiamdari, Rina Sri (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2023)
Oil palm is the main vegetable oil-producing crop in Indonesia. Leaf spot disease is one of the major diseases that attacks oil palm seedlings at all seedling stages. In Indonesia, leaf spot disease in oil palm nurseries is most commonly caused by the genus Curvularia with an infection intensity of up to 60–70%. The control of leaf spot disease usually uses chemical fungicides but its continuous use can cause the development of resistant pathogen fungi and have a long-term negative impact on the environment. False elder (Peronema canescens Jack) leaves have bioactivity as an antimicrobial control disease caused by fungal infections. In this study, Curvularia was isolated from oil palm seedlings infected with leaf spot disease from oil palm nurseries in South Sumatra. Effectiveness testing of P. canescens leaves conducted by a Completely Randomized Design method with five treatments and three replications. The fungi that caused leaf spot disease in oil palm were identified as Curvularia eragrostidis. P. canescens leaf water extract at 25% concentration was very ineffective to quite effective in controlling disease severity based on the average number of spots and diameter of spots in oil palm with the values 36.25–59.50% and 12.50–27.78%. P. canescens leaf water extract could reduce the average number of spots and diameter of spots started on day 30 after being sprayed three times with P. canescens leaf water extract so that it could be used as an alternative to control C. eragrostidis leaf spot disease in oil palm that is more friendly to the environment.